2022
DOI: 10.3390/d14020120
|View full text |Cite
|
Sign up to set email alerts
|

Solenysa, a Cretaceous Relict Spider Group in East Asia

Abstract: A time scale of phylogenetic relationships contributes to a better understanding of the evolutionary history of organisms. Herein, we investigate the temporal divergence pattern that gave rise to the poor species diversity of the spider genus Solenysa in contrast with the other six major clades within linyphiids. We reconstructed a dated phylogeny of linyphiids based on multi-locus sequence data. We found that Solenysa diverged from other linyphiids early in the Cretaceous (79.29 mya), while its further divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Subsequent molecular work that used the same genes but with a much larger taxon sample (Dimitrov et al 2012, 2017; Wang et al, 2015; Tian et al, 2022) has corroborated many of those groups but also suggested a much more complex picture of the phylogeny of Linyphiidae. All more recent analyses have confirmed the hypothesis of Arnedo et al (2009) that micronetines are paraphyletic.…”
Section: Introductionmentioning
confidence: 90%
“…Subsequent molecular work that used the same genes but with a much larger taxon sample (Dimitrov et al 2012, 2017; Wang et al, 2015; Tian et al, 2022) has corroborated many of those groups but also suggested a much more complex picture of the phylogeny of Linyphiidae. All more recent analyses have confirmed the hypothesis of Arnedo et al (2009) that micronetines are paraphyletic.…”
Section: Introductionmentioning
confidence: 90%
“…Many factors can be at play, including diversification and extinction tempos. In a paper titled "Solenysa, a Cretaceous Relict Spider Group in East Asia" [4], Jiahui Tian and colleagues explore the long evolutionary history of one of the major clades of linyphiids and the reasons for its relative poverty in species diversity compared with the other linyphiid lineages. The authors found that Solenysa diverged from other linyphiids in the Cretaceous and underwent diversification stasis well into Oligocene.…”
Section: Phylogenomic and Evolutionary Research Trends In Arachnologymentioning
confidence: 99%